1998
DOI: 10.1016/s0304-3959(98)00094-3
|View full text |Cite
|
Sign up to set email alerts
|

Spinal bicuculline produces hypersensitivity of dorsal horn neurons: effects of excitatory amino acid antagonists

Abstract: In this study, we sought to characterize the effects of focal GABA(A) receptor antagonism on spontaneous and evoked activity in dorsal horn neurons of the alpha-chloralose anesthetized cat. Bicuculline (0.5, 1.0 mM) applied near the neurons through a transparenchymal dialysis fiber resulted in increased evoked activity in nociceptive dorsal horn neurons. Hair deflection was the stimulus most affected, followed by both low and high threshold tonic mechanical stimulation of the receptive field. In addition, neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 37 publications
4
53
1
Order By: Relevance
“…The difference between the studies of Abdin et al (2006) and the current study is likely due to the intensity of the mechanical stimuli used. Spinal GABA A and glycine receptors inhibit tactile allodynia (Sivilotti and Woolf, 1994;Sorkin et al, 1998), but only GABA A receptors inhibit hypersensitivity to high intensity stimuli (Sorkin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the studies of Abdin et al (2006) and the current study is likely due to the intensity of the mechanical stimuli used. Spinal GABA A and glycine receptors inhibit tactile allodynia (Sivilotti and Woolf, 1994;Sorkin et al, 1998), but only GABA A receptors inhibit hypersensitivity to high intensity stimuli (Sorkin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, noxious input can quickly enhance the sensitivity of spinal neurons for further C-fiber inputs. Spinal neuronal excitability may increase through several mechanisms including: 1) a cumulative depolarization that lowers the threshold for action potential initiation (induced by increased spontaneous or ongoing activity of primary afferents) (Sivliotti et al 1993), 2) presynaptic facilitation (e.g., increased excitatory amino acid or tachkinin release evoked by prior primary afferent activation) (Gerber and Randic 1989;Urban and Randic 1984;Yoshimura and Jessell 1990), and 3) increased efficacy of postsynaptic receptors induced by prior activation of spinal neurons (e.g., because of facilitation of signal transduction/second messenger coupling and/or receptor upregulation) (Schmidt 1971;Sorkin and Puig 1996;Sorkin et al 1998). In the present study, increased WDR neuronal excitability likely resulted from the summation of depolarizing postsynaptic potentials in WDR neurons and/or presynaptic facilitation because these changes can occur within minutes, whereas an increase in postsynaptic receptor number or efficacy takes much longer.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the first-order thalamic relay, which provides numerous terminations in L4 (Sorkin et al, 1998;Gil et al, 1999;Sherman and Guillery, 2002;Bruno and Sakmann, 2006), in fact contacts L6 pyramidal neurons predominantly on Figure 11. Activation of distal inhibitory inputs induces a long-lasting blockade of dendritic Ca 2ϩ electrogenesis.…”
Section: Implications For L6 Pyramidal Neurons In the Neocortical Cirmentioning
confidence: 95%